2003
DOI: 10.1002/chin.200345018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P2O5 and AlPO4 Coating on LiCoO2 Cathode Material.

Abstract: The thermal stability and electrochemical properties of P 2 O 5 -and AlPO 4 -coated LiCoO 2 powders are compared with those of bare LiCoO2. During 12 V overcharge tests in Li ion cells, the coated samples do not exhibit thermal runaway and the cell surface temperature remains below 120°C, whereas the bare sample explodes and the cell surface temperature reaches 450°C. The AlPO 4 -coated sample shows excellent electrochemical properties compared to those of P 2 O 5 -coated and bare LiCoO 2 . -(CHO*, J.; LEE, J.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…38 It is also known that DAP can be thermally decomposed to P 2 O 5 above 400 °C. 39 Hence, the actual product that reacted with the Li residues is P 2 O 5 , not DAP. The P 2 O 5 −Li residue−O 2 phase diagram in Figure 6b Table I According to the analysis of the product phases in the reactions of the MPs with the Li residues, Li 3 PO 4 is a frequently generated phase, as shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…38 It is also known that DAP can be thermally decomposed to P 2 O 5 above 400 °C. 39 Hence, the actual product that reacted with the Li residues is P 2 O 5 , not DAP. The P 2 O 5 −Li residue−O 2 phase diagram in Figure 6b Table I According to the analysis of the product phases in the reactions of the MPs with the Li residues, Li 3 PO 4 is a frequently generated phase, as shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond biological concerns, phosphate adsorption on metal oxides is critical to investigate, since industrial LCO surface coatings incorporate phosphorus as the amorphous LiPON, or as an ordered metal phosphate such as AlPO 4 . It has been demonstrated that the functional properties and chemical behavior of LCO nanoparticles improve with these surface adsorbed coating layers, as the coating can enhance directed ionic transfer, act as a scavenger for HF released from solid state electrolytes, and act as a chemically stable barrier to protect the LCO surface from attack in aqueous environments. …”
Section: Introductionmentioning
confidence: 99%
“…Among them, surface coating is considered to be the most effective method without the sacrifice of specific capacity. There are many coatings, such as binary oxides (e.g., Al 2 O 3 , , ZnO, , ZrO 2 , , MgO, SnO 2 , and TiO 2 , ), metal phosphates (e.g., AlPO 4 ), and metal fluorides (e.g., LiF , and MgF). ZnO has been recognized to be a proper material for improving the cycling stability of layered LiCoO 2 cathodes at high cutoff voltages. , In a previous study, Fang et al .…”
Section: Introductionmentioning
confidence: 99%